Evolution of forensic psychiatry in Italy over the past 40 years (1978–2018). (January 2019) - Ferracuti, Stefano; Pucci, Daniela; Trobia, Federico; Alessi, Maria Chiara; Rapinesi, Chiara; Kotzalidis, Georgios D.; Del Casale, Antonio
Abstract: In Italy, following the closure of psychiatric hospitals in 1978 and the release of psychiatric patients into community care, there was a mismatch between common psychiatric patients and the convicted mentally ill who were sentenced to serve in state forensic psychiatric hospitals. The recent closure of such structures following the Prime Minister's Decree of April 1, 2008, fostered the need to create new structures. These are called "REMS, " and they are based in the community and led by psychiatrists and healthcare staff who may rely on the collaboration of public security staff. This act completed a course of progressive deinstitutionalization of all psychiatric patients. However, some problems remain, and persons regarded as "partially mentally disabled" at the time of crime perpetration must serve part of their sentence in prison and the rest in the aforementioned structures or in psychiatric rehabilitation communities, depending on their claimed "social dangerousness." Psychiatric services now face the ambiguity of treating persons who are considered dangerous by court orders, while the civil law criteria for involuntary hospitalization is based only on the need of care. The complete closure of forensic hospitals may be considered a decisive step forward in the humanization of society, but there are still some issues to address to make it work better. The implementation of multidisciplinary teams and effective psychotherapy, psychoeducational, and rehabilitation interventions can help. Highlights: The 4-1-2008 Presidential Decree closed forensic psychiatric hospitals in Italy. Alternative structures for the mentally ill convicted were thus instituted. New issues emerged as a consequence, for example, social dangerousness. The new act completed the deinstitutionalization that started in 1978.